APLIKASI SCRATCH BERBASIS PENDIDIKAN KARAKTER UNTUK MENINGKATKAN BERPIKIR KREATIF MATEMATIK DI ERA SOCIETY 5.0 - M. Afrilianto; Tina Rosyana; Linda Linda (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Character is very important to foster the personality of students. Character education can be realized through mathematics learning activities using the initial Android application according to the technological development society in the 5.0 era. In research conducted. This study aims to analyze the development of the scratch application and the improvement of student’s mathematical creative thinking after using the scratch application. The method used is R&D (Research and Development)  with the Plomp model through the initial investigation stage, product design, and field testing. The subject of this study was to find seventh grade students at SMPN 3 Darma, Kuningan, West Java. The instrument used in the form of 5 items of description test, validation, analysis, and interviews which were collected online through Google Form. In this study it was found that; 1) Scratch application that is prepared is of good quality, has valid, practical, and effective criteria, 2) Scratch application is effective for mathematical creative thinking skills, 3) Student and teacher responses to scratch application are very positive. So the scratch application can help and make it easier for students to learn and is very good to continue to be developed.